Calspermin gene transcription is regulated by two cyclic AMP response elements contained in an alternative promoter in the calmodulin kinase IV gene. - Sun, Z (1995)
The transcript for the high-affinity Ca2+/calmodulin-binding protein calspermin is generated from the gene encoding Ca2+/calmodulin-dependent protein kinase IV only in postmeiotic germ cells during spermatogenesis. We demonstrate that this testis-specific calspermin transcript can be produced in heterologous cells by utilization of a promoter located in an intron of the calmodulin (CaM) kinase IV gene. Critical motifs within this promoter are two cyclic AMP response element (CRE)-like sequences located about -70 and -50 bp upstream of the transcriptional initiation site. Both CRE motifs are footprinted by the authentic testis-specific transcriptional activator CREM tau or by CREM tau present in adult testis nuclear extract. Whereas a 2.1-kb DNA fragment containing the calspermin promoter is inactive when transfected into NIH 3T3 cells, activity can be restored by cotransfection of CREM tau and protein kinase A or CaM kinase IV but not CaM kinase II alpha. Restoration of activity is greatly reduced by mutation of the two CRE motifs. Since CRE-like motifs have been identified in many genes uniquely expressed in postmeiotic germ cells, which contain abundant CREM tau protein, we suggest that CREM tau may function as one transcription factor responsible for the expression of postmeiotic germ cell-specific genes.